Impact of Office Physical Work Environment on the Productivity Level of Employees of Northpoint Development Bank in Caloocan Branch: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The physical working environment is the overall layout and design of the offices andworkstations. Many physical work environment studies have shown workers are satisfiedwith specific workspace features. Numerous studies also have consistently demonstratedthat characteristics of the physical work environment can significantly affect employees'behavior, perceptions, and productivity. These features' preferences by users are highlysignificant to their productivity and workspace satisfaction.Secondary data were collected and analyzed to achieve the study objective and for thepurpose of this study. This study utilized the Pearson correlation coefficient to measure thestatistical relationship between two variables. The independent variable is the physical workenvironment, including lighting, noise, temperature, office space/layout, and furniture design,while the dependent variable is the employees' productivity.Moreover, the result of the hypothesis found that there is no significant relationship betweenthe physical work environment and employees' productivity. However, the researchers stillrecommended the management make some changes to their workplace to improve all thefactors that this study used to improve employees' productivity. In addition, researcherspresented a pictorial layout plan for their workplace's physical environment so thatemployees could remain productive at all times.
Keywords: Business Administration